Insecticidal activity of filtrate of Beauveria bassiana cultures incubated under the temperatures of 25°C and 34 °C against larvae Spodoptera litura. Issue 1 (March 2020) - Herlinda, S; Fajriah, A J; Suparman; Anggraini, E; Elfita; Setiawan, A; Verawaty, M; Hasbi; Arsi
Abstract: Beauveria bassiana has been widely used to control lepidopteran larvae, such as Spodoptera litura. The objective of this research was to observe the mortality and median Lethal Time (LT50 ) of larval S. litura after exposure of filtrate of B. bassiana cultures incubated under temperatures of 25° and 34°C. The isolates used were 10 isolates of B. bassiana and they were incubated under temperatures 25 and 34 °C in liquid media for 6 wk. The results showed that the highest mortality caused by B. bassiana was found on the fungus incubated under 25 °C and was significantly different from that of temperature 34 °C. The shortest LT50 of larval S. litura was found on the fungus incubated under temperature 25 °C and was significantly different from that of temperature 34 °C. The highest mortality was found on isolate BTmPc (96%) incubated under temperature 25 °C with the shortest LT50 (7.51 d), which was not significantly different from isolate BTmTr (93.33%) incubated under temperature 25°C with the LT50 (7.31 d). Therefore, isolate BTmTr incubated under temperature 25 °C was the most effective on killing S. litura larvae. However, isolate of BMkMs incubated under 34 °C was still caused the highest percentage of larval mortality (18.67%) and the shortest LT50 (16.20 d). Therefore, the BMkMs isolate can be developed into bio-insecticide active ingredients for controlling S. litura in tropical ecosystem.